Secure authentication scheme in 6G‐enabled mobile Internet of things for online English education. Issue 5 (6th August 2022) - Yin, Jiming; Cui, Jie
Abstract: In recent years, the mobile Internet of Things (MIoT) for online English education has quickly become an important means and main tool for people to learn and communicate English due it has characteristics and advantages such as high efficiency and no geographical restrictions. However, most MIoT for online English education is vulnerable to security attacks because of the online learning device's weak security protection measures and their communication channels with open wireless nature. To address these issues, herein, a novel secure authentication scheme in 6G‐enabled MIoT for online English education is proposed. The proposed authentication scheme does not rely on the ideal tamper‐proof device. In this scheme, the certificate and key are updated in real‐time to resist side‐channel attacks, and pseudonym seeds are used to generate pseudonyms to hide user's identity information and realise identity privacy protection. The scheme allows the attacker to continuously obtain private key information. Detailed security analysis proves that the authors' scheme is unforgeable to adaptive selection message attacks and can satisfy the security requirements of 6G‐enabled MIoT for online English education. In addition, compared with other related studies, the proposed scheme achieves better performance in terms of computation and communication costs.